2022
DOI: 10.3390/fermentation8030133
|View full text |Cite
|
Sign up to set email alerts
|

Revalorization of Cava (Spanish Sparkling Wine) Lees on Sourdough Fermentation

Abstract: Cava lees are a sparkling wine by-product formed of dead microorganisms, tartaric acid and other inorganic compounds, with a potential for enhancing microbial growth. Lees are rich in antioxidant compounds as well as β-glucans and mannoproteins. The aim of this study was to evaluate the effect of different concentrations of cava lees (0–2% w/w) on the microbiota (LAB and yeasts) responsible for sourdough fermentation (8 days) to revalorize this by-product of the wine industry. The results showed that 2% cava l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…It was observed that, with the addition of Cava lees, there was a greater production of volatile compounds ( Table 1 ), including the products of microbial metabolism. In fact, previous studies have focused on the effect of Cava lees on the growth and survival of LAB, concluding that they have a positive effect on the fermenting microbiota [ 14 , 20 , 21 ]. Therefore, higher microbial populations in formulations with Cava lees might induce greater concentrations of volatile compounds as a consequence of LAB and yeast fermentation in sourdough.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was observed that, with the addition of Cava lees, there was a greater production of volatile compounds ( Table 1 ), including the products of microbial metabolism. In fact, previous studies have focused on the effect of Cava lees on the growth and survival of LAB, concluding that they have a positive effect on the fermenting microbiota [ 14 , 20 , 21 ]. Therefore, higher microbial populations in formulations with Cava lees might induce greater concentrations of volatile compounds as a consequence of LAB and yeast fermentation in sourdough.…”
Section: Discussionmentioning
confidence: 99%
“…The highest values were reached at 2% Cava lees ( p < 0.05), which may be due to higher survival rates among the microorganisms fermenting the sourdough. In fact, it has recently been reported that Cava lees have a growth-promoting effect on different species of LAB in vitro and in sourdough [ 14 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The titratable acidity (TA) results showed no significant variations over 21 days. The stability of the acidity could suggest a buffered environment that can be supported by the mannoprotein content of the wine lees, resulting from the autolysis of the cell walls of the yeasts that participate in the fermentation processes [6,46,47]. The increase in total soluble solids (TSS) with the addition of WL (1.5% and 2%) can be attributed to the dietary fiber composition of lees, considering the primary element in their composition and also the maltodextrin included in the product formulation.…”
Section: Physicochemical Parametersmentioning
confidence: 99%
“…In addition to the healthy tendency in consumption, there is a current trend in the food and beverage industry to reduce waste based on the valorization of by-products, and co-products, that contribute to a circular economy and sustainability in production [6].…”
Section: Introductionmentioning
confidence: 99%